Prevalence of dual sensory impairment in veterans: a rapid systematic review - Raza, Zara; Hussain, Syeda F.; Gomes, Renata S. M. (Frontiers in Rehabilitation Sciences, 2024)
It is a well-known fact that dual sensory impairment (DSI) is particularly prevalent in the older population. Military-associated DSI, however, has not been as extensively explored. Estimates of prevalence in veteran populations are scarce in comparison to the general population. This review aimed to provide an overview of studies that have reported a prevalence rate for veterans. Factors e.g. traumatic brain injury, blast exposure and age were identified as potential contributors to an increased prevalence rate in this population, and only one study was found to measure the outcomes of DSI in veterans. Overall, this review identified a lack of universal definition for DSI that is based on clinical measures, and that most studies calculated a prevalence rate in a specific subsect of veterans in the United States. DSI is a disability that affects a significant proportion of the population, and veterans are at particular risk, regardless of age. This review shows that defining and identifying DSI cases is key to obtaining the true prevalence rate. Determining true prevalence is key in establishing targeted policies and support provision. This review therefore fits the scope of this journal, as it identifies military-related factors for DSI and gaps in veterans' disability research.